François Pierre de la Varenne, Englished by I.D.G.: The French Cook - Jaine, Tom (Petits Propos Culinaires, 2024)
François Pierre de la Varenne, Englished by I.D.G.: The French Cook: Introduced by Philip and Mary Hyman: Southover Press, Lewes, 2001: ISBN 1-870962-17-6: 261 pp., glossary, index, h/b, £22.